MR1-Restricted T Cells Are Unprecedented Cancer Fighters - Vacchini, Alessandro; Chancellor, Andrew; Spagnuolo, Julian; Mori, Lucia; De Libero, Gennaro (Frontiers in Immunology, 2020)
Non-polymorphic MHC class I-related molecule MR1 presents antigenic metabolites to mucosal-associated invariant T (MAIT) cells and self-antigens to MR1-restricted T cells (MR1T). Both MR1-restricted T cell populations are readily identified in healthy individuals, with MAIT cells accounting for 1-10% of circulating T cells, while MR1T cells have frequencies comparable to peptide-specific T cells (<0.1%). Self-reactive MR1T cells display a heterogeneous phenotype, and are capable of releasing both TH1 and TH2 cytokines, supporting not only activation of inflammation but also contributing to its regulation. Importantly, MR1T cells recognize and kill a diverse range of MR1-expressing tumor cells. On the other hand, evidence suggests MAIT cells augment cancer growth and metastases. This review addresses the potential role of MR1-restricted T cells in controlling tumor cells, facilitating their elimination and regulating cancer immunity. We also discuss therapeutic opportunities surrounding MR1-restricted T cells in cancer.